LEP Language Disability, Immigration Reform, and English-Language Acquisition - Dávila, Alberto; Mora, Marie T. (American Economic Review, 2016)
Policy might partly shape the English-language acquisition of Hispanics migrating to the U.S. mainland, particularly policies related to limited-English-language disability benefits and immigration reform. Using data from the American Community Survey, we find that island-born Puerto Ricans on the U.S. mainland, as U.S. citizens, may have lower incentives to learn English than Hispanic immigrants because of their higher participation in LEP disability programs. However, among Mexican immigrants, recent immigration reform aimed at interior enforcement might have increased incentives for Mexican immigrants to learn English to reduce their probability of detection, if speaking English proxies for undocumented status.